A non‐isolated quasi‐Z‐source‐based high‐gain DC–DC converter. (25th October 2021) - Mahmood, Arshad; Zaid, Mohammad; Khan, Shahrukh; Siddique, Marif Daula; Iqbal, Atif; Sarwer, Zeeshan
Abstract: To overcome the problems associated with Z‐source‐based DC–DC converters, a quasi‐Z‐source (QZS)‐based high‐gain DC–DC boost converter with switched capacitors is proposed in this work. Z‐source‐based DC–DC converters have problems like low‐voltage gain, discontinuous input current, and high‐voltage stress on the active and passive components. The proposed converter can produce a high‐voltage gain of more than 10 times for a duty cycle of less than 0.5. The converter has other desirable features like reduced voltage stress across the switching components and continuous input current (CIC). It comprises a QZS cell made up of switched inductors and a voltage multiplier cell (VMC) made up of switched capacitors. The power loss analysis is done using PLECS software by incorporating the real parameters of switches and diodes from the datasheet. A hardware prototype of 200 W is developed in the laboratory to verify the working of the converter. In experimental results for an output power of 200 W, the converter is operated with a source voltage of 33 V at a duty ratio of 0.4 providing an output voltage of 395 V. The converter performance is good in open‐loop conditions and is verified through experimental results. Abstract : The proposed quasi‐Z‐source (QZS) converter introduced in this paper can produce a high‐voltage gain of more than 10 times for a duty cycle of less than 0.5. The converter has other desirable features like reduced voltage stress across the switching components and continuous input current (CIC). From experimental results, the converter performance is found to be good in open‐loop conditions.